Developing socio-scientific inquiry-based worksheets to enhance students’ problem-solving skills on biodiversity topics - Raini Dahriana Pulungan; Ummi Nur Afinni Dwi Jayanti; Erna Wijayanti (Universitas Muhammadiyah Malang, 2025)
This study was motivated by the limitations of conventional teaching methods, which fail to effectively support the development of students’ problem-solving skills, as well as by the lack of teacher understanding regarding the Socio-Scientific Inquiry-Based Learning (SSIBL) model. These issues contribute to students’ low academic achievement, particularly in the topic of biodiversity. This research aimed to develop a student worksheet (LKPD) based on the SSIBL model to enhance students’ problem-solving abilities in biodiversity learning. Using a Research and Development (R&D) approach, the study employed the ADDIE model, comprising analysis, design, development, implementation, and evaluation stages. The research involved 30 tenth-grade science students (Class X-IPA 1) at SMA Al-Ulum Terpadu, Medan. Data were collected through interviews, needs assessments, expert validation, student response questionnaires, and problem-solving tests. Expert validation results indicated that the SSIBL-based LKPD was both valid and practical. The implementation phase demonstrated a significant improvement in students’ problem-solving performance, as evidenced by their post-test scores. Moreover, the SSIBL-based learning approach nurtured students’ critical awareness of socio-environmental issues and strengthened their scientific decision-making abilities. These findings highlight the effectiveness of SSIBL-based LKPD as an innovative teaching tool that supports the development of 21st-century skills, particularly in biology education.